Atributos microbiológicos e enzimáticos do solo como indicadores de qualidade em sistema plantio direto e terraceamento agrícola - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Soil is a component of the biosphere with local, regional and global effects, performing essential functions for life. Soil degradation represents a threat to food production systems and highlights the importance of agricultural systems. Thus, assessing soil quality is an important indicator of good crop yields in various land use contexts. Terracing, for example, can contribute to improving soil health and ecosystem services, enabling more sustainable agriculture. The objective of this work was to evaluate biological parameters in megaplots under no-tillage system, with and without terracing, as soil quality indicators. The experiment was conducted in 2020 at the Fazenda Escola “Capão da Onça” belonging to the State University of Ponta Grossa (UEPG), Campos Gerais region. The study area comprises an extension of 3.08 ha-1 in a watershed in the Upper Tibagi River, subdivided into two megaplots of 1.604 ha-1 and 1.476 ha-1. The experiment was conducted using a strip model, with 12 replications, with treatments comprising: 1°) Areas (CT - presence of terraces ST - absence of terraces) and 2°) Fractions of the areas of (Upper third, middle and bottom). The biological attributes evaluated were: microbial biomass carbon (C-BM), microbial biomass nitrogen (N-BM), basal respiration (RB), metabolic quotient (qCO2), easily extractable glomalin (GFE), urease (U) and acid phosphatase (FA). The evaluations showed that the treatments had a significant effect (p<0.05), in isolation or in interaction, on all evaluated biological attributes. Thus, the presence of terraces (mega A) and the differences in the toposequence of the sampled areas influenced the microbial biomass, metabolic and enzymatic activity, and glomalin of the analyzed soils, presenting the best results in the present study. In turn, the interaction between the megaplot x toposequence factors significantly interfered only with the biological attributes: N-BM, GFE and FA activity. It is concluded that the biological attributes are sensitive to indicate and differentiate the soil management used in agricultural areas.
Keywords: Indicadores biológicos; Terraços; Conservação do solo; Biological indicators; Terraces; Soil conservation; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA